2019 Papua New Guinea economic survey. Issue 3 (2nd October 2019) - Howes, Stephen; Fox, Rohan; Laveil, Maholopa; Nguyen, Bao H.; Sum, Dek Joe
Abstract: Although official statistics show that an economic recovery is underway in Papua New Guinea, the country's new Prime Minister has stated that the economy is "bleeding and struggling." Disappointing 2019 first‐half‐year revenue results and the reintensification of foreign exchange shortages suggest that last year's (nonresource) recovery, which was based on unsustainable fiscal expansion, has not endured; that this year's growth statistics may need to be further revised downwards; and that the government's growth and fiscal challenges are once again intensifying. The new government's governance reforms are promising; but they are no substitute for reviewing exchange rate and fiscal policy, perhaps by turning to the International Monetary Fund for advice and support to address the problems it has inherited, including in relation to arrears, guarantees, and state‐owned enterprise debt.